To the Arctic, For the Arctic - Anderson, Tracey L. (Earth Common Journal, 2012)
To the Arctic (Judson, MacGillivray & MacGillivray, 2011), the new documentary in IMAX format, which stands for Image Maximum, “a motion picture format with the capacity for greater size and clearer resolution than standard movie systems” (Tech-FAQ, 2012), reveals the verifiable impacts of global warming on the Arctic so that humans can see and hear them up close.